Pendidikan Kesehatan Digital Melalui E-Komik: Meningkatkan Pengetahuan Remaja tentang Risiko Merokok - Devi Trianingsih; Nirina Arlly Nabila; Gaung Eka Ramadhan; Exsos Grend Dais; Fajriyah Nur Afriyanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Smoking behavior among adolescents remains a serious public health problem, especially among high school students who often do not understand the long-term impacts. Digital learning media offers a new, more engaging and youth-appropriate way to deliver health education. This study aims to assess the effectiveness of an e-comic-based health education intervention in improving the knowledge of eleventh-grade students about the dangers of smoking. The e-comic used has been officially registered with HAKI under number EC002025160224. The study used a quasi-experimental one-group pretest–posttest design with 79 respondents who met the inclusion criteria. The questionnaire instrument was validated and demonstrated high reliability with a Cronbach's alpha value of 0.892. Univariate and bivariate analyses were conducted to assess changes in knowledge. The average pretest score of 10.71 (SD = 2.22) indicated low to moderate initial knowledge, while the posttest score increased to 18.87 (SD = 1.11). The Wilcoxon Signed Rank test showed a significant difference between the two scores (p = 0.001). These results prove that IPR-enabled e-comics are effective in increasing adolescents' knowledge about the dangers of smoking, so that creative digital media can be an important strategy in smoking prevention efforts in schools.